2013
DOI: 10.2298/abs1304317m
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in lymph nodes and spleen upon EAE induction in C57BL/6 mic

Abstract: Myelin oligodendrocyte glycoprotein (MOG) is a protein widely used in the induction of experimental autoimmune encephalomyelitis (EAE) for studying human multiple sclerosis (MS). In C57BL/6 female mice aged eight weeks, we administered subcutaneously MOG35-55 peptide in CFA (complete Freund?s adjuvant) along with pertussis vaccine injected intraperitoneally. We observed the sign of flaccid tail as early as thirteen days post-immunization in five of twelve animals. Hematoxylin and eosin staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…9,15,16 Due to its cytotoxic and immunosuppressive effects, CP is commonly used against a broad spectrum of cancers, including lymphoma, chronic lymphocytic leukemia, soft tissue and osteogenic sarcoma, several solid tumors, and autoimmune diseases. [17][18][19][20] Besides clinical applications, CP is also widely used in experimental research to induce immunodeficiency in animal models. 11,21,22 CP has been used to study numerous immune processes related to cancer development, transplant tolerance/ rejection, and infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,15,16 Due to its cytotoxic and immunosuppressive effects, CP is commonly used against a broad spectrum of cancers, including lymphoma, chronic lymphocytic leukemia, soft tissue and osteogenic sarcoma, several solid tumors, and autoimmune diseases. [17][18][19][20] Besides clinical applications, CP is also widely used in experimental research to induce immunodeficiency in animal models. 11,21,22 CP has been used to study numerous immune processes related to cancer development, transplant tolerance/ rejection, and infections.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its cytotoxic and immunosuppressive effects, CP is commonly used against a broad spectrum of cancers, including lymphoma, chronic lymphocytic leukemia, soft tissue and osteogenic sarcoma, several solid tumors, and autoimmune diseases. 17 20…”
Section: Introductionmentioning
confidence: 99%
“…Irla et al 42 proposed that MHCII expression by pDCs confers natural protection against EAE by stimulating the selective expansion of myelin-Ag-specific natural regulatory T cells in secondary lymphoid tissues. In our previous study we suggested that pDCs might be the one to make a connection between mild clinical signs expressed in the myelin oligodendrocyte glycoprotein (MOG) variant of EAE-induced mice and the expression of MHC class II molecules in the secondary lymphoid organs 43 . Activation of DCs leads to their maturation, that is, upgrades the expression of MHC class II as well as co-stimulatory molecules (CD80, CD86, CD40).…”
Section: Pathophysiological Concepts Of Multiple Sclerosis With Respementioning
confidence: 99%